COMPUTED-TOMOGRAPHY AND MAGNETIC-RESONANCE-IMAGING IN 3 PATIENTS WITH TOLOSA-HUNT SYNDROME - (:unkn) unknown (KARGER, 1993)
Three patients with Tolosa-Hunt syndrome were examine by computed tomography (CT) and magnetic resonance imaging (MRI). CT of the brain did not reveal any definite abnormality in any of the patients. MRI demonstrated an abnormal soft tissue area in the cavernous sinus in only 1 patient. There was clinical improvement after corticosteroid therapy. MRI is mandatory for demonstrating lesions in the cavernous sinus or in the superior orbital fissure in patients with THS.
Keywords: TOLOSA-HUNT SYNDROME; MAGNETIC RESONANCE IMAGING; COMPUTED TOMOGRAPHY